Structural, Elastic, and Multiferroic property of strontium ferrite nanoceramic prepared by sol–gel derived citrate precursor method. (2021) - Sonu Kumar, Singh; Kumar Singh, Rakesh; Kumar, Nishant; Kumar, Gaurav; Shankar, Uday
Abstract: Strontium hexaferrite (M−type) nanoceramic is synthesized using citrate precursor sol–gel process. The Intensity of the X-ray diffraction pattern confirms that the prepared nanomaterial i.e. SrFe12 O19 is in pure phase along with the presence of some impurity at annealing temperature 850 °C, which got eliminated by enhancement of 950 °C annealing temperature. The XRD measurement shows SrFe12 O19 possesses a hexagonal crystal structure having space group P6/MMC. For estimating crystallite size, we used the W-H plot and found it to be 56.825 nm and 67.366 nm for 850 °Cand 950 °C, temperature respectively. Increasing annealing temperature results in an increment in grain size and lattice parameters due to induced strain, a gradual decrease in broadening of XRD peak is observed. SEM measurement supports the XRD results and indicates that the sample possesses some agglomeration, which may be due to enhancement in annealing temperature and interparticle interaction. FTIR was used for estimating force constant, bond length, and functional group present in the prepared materials. Force constant increases while bond length decreases with the increased annealing temperature. The elastic property evaluated seems to reduce by enhancement of the increasing value of annealing temperature for strontium hexaferrite sample. The Increasing Value of annealing temperature leads to a reduction in polarization value with the broadening of multiferroic loops suggesting a noticeable reduction in electrical leakage.